1983
DOI: 10.1126/science.6316502
|View full text |Cite
|
Sign up to set email alerts
|

Productive Infection and Cell-Free Transmission of Human T-Cell Leukemia Virus in a Nonlymphoid Cell Line

Abstract: Human T-cell leukemia virus (HTLV), American PL isolate, was transmitted by cocultivation and by cell-free filtrates to a nonlymphoid human osteogenic sarcoma (HOS) cell line, designated HOS/PL, but not to nine other lines bearing receptors for HTLV. HOS and HOS/PL cells are not dependent on interleukin-2 and do not express interleukin-2 receptors that are recognized by anti-Tac monoclonal antibody. HTLV released by the Japanese MT2 cell line was also transmitted to HOS cells. The infected HOS cells release su… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
84
1

Year Published

1984
1984
2007
2007

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 205 publications
(87 citation statements)
references
References 19 publications
2
84
1
Order By: Relevance
“…Retroviruses may induce cell fusion without the occurrence of viral replication (38). Indeed, most mammalian cell lines susceptible to fusion when cultured with C91/PL are not permissive for viral replication (27). We therefore sought to determine whether HTLV-I is capable of penetrating and replicating within endothelial cells by detecting their capacity to produce viral antigens.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Retroviruses may induce cell fusion without the occurrence of viral replication (38). Indeed, most mammalian cell lines susceptible to fusion when cultured with C91/PL are not permissive for viral replication (27). We therefore sought to determine whether HTLV-I is capable of penetrating and replicating within endothelial cells by detecting their capacity to produce viral antigens.…”
Section: Resultsmentioning
confidence: 99%
“…Moreover, viral pseudotypes bearing HTLV-I or HTLV-II envelope glycoproteins can penetrate a variety of mammalian cell lines (24). In several of these susceptible cells, syncytia were induced by cocultivation with HTLV-I-producing cells (25,26) and in a single human osteosarcoma cell line stable HTLV-I replication could be demonstrated (27).…”
mentioning
confidence: 99%
“…In vitro and in vivo tropism of HTLV-1 Studies documenting in vitro infection and dissemination of HTLV-1 to non-T cells, including nonlymphoid cells, were published soon after the identification of HTLV (Yamamoto et al, 1982b;Clapham et al, 1983;Hayami et al, 1984). Productive transmission of natural HTLV-1 isolates to primary human endothelial cell cultures (Ho et al, 1984;Hoxie et al, 1984), monocyte and microglial cells (Hoffman et al, 1992), as well as basal mammary epithelial cells (LeVasseur et al, 1998) has been reported.…”
Section: Htlv-1 Tropism: In Vitro or In Vivo Veritas?mentioning
confidence: 99%
“…As discussed more thoroughly in the following section, ATLV/HTLV can infect not only human lymphocytes but also non-human cells. Clapham et al (1983) obtained a HTLV-positive cell line, HOS/PL, by the co-culture of the human osteogenic sarcoma line HOS with the HTLV-carrying C91/PL cell line. Cell-free virus derived from this (unpublished).…”
Section: Cell-lree Viral Ir!ti'ctionmentioning
confidence: 99%